e-Turist: An Intelligent Personalised Trip Guide (Informatica, 2016)
We present e-Turist, an intelligent system that helps tourists plan a personalised itinerary to a tourist area, taking into account individual’s preferences and limitations. After creating the route, e-Turist also offers real-time GPS guidance and audio description of points of interest visited. Here we focus on two main components, the recommender system and the route planning algorithm. We also present some use cases to highlight e-Turist functionalities in different configurations.